A Comprehensive in vitro and in silico Analysis of Nematicidal Action of Essential Oils - Kundu, Aditi; Dutta, Anirban; Mandal, Abhishek; Negi, Lalit; Malik, Monika; Puramchatwad, Rajshekhar; Antil, Jyoti; Singh, Anupama; Rao, Uma; Saha, Supradip; Kumar, Rajesh; Patanjali, Neeraj; et al. (Frontiers in Plant Science, 2021)
Nematicidal potential of essential oils (EOs) has been widely reported. Terpenoids present in most of the essential oils have been reported responsible for their bioactivity though very less is known about their modes of action. In the present study, an in vitro screening of nine EOs namely, Citrus sinensis (OEO), Myrtus communis (MTEO), Eucalyptus Citriodora (CEO), Melaleuca alternifolia (TEO), Acorus calamus (AEO), Commiphora myrrha (MREO), Cymbopogon nardus (CNEO), Artemisia absinthium (WEO) and Pogostemon cablin (PEO) against Meloidogyne incognita revealed OEO, CNEO and TEO as most effective with LC50 39.37, 43.22 and 76.28 µg mL-1 respectively.. EOs had varying compositions of mono- and sesquiterpenes determined by gas chromatography-mass spectrometry (GC-MS) analysis. The in silico molecular interactions screening of major EO constituents and the seven selected target proteins of the nematode indicated highest binding affinity of geraniol-ODR1 (Odorant Response Gene 1) complex (ΔG =-36.9 kcal mol-1), due to extensiveH-bonding, hydrophobic and π-alkyl interactions. The relative binding affinity followed the order: geraniol-ODR1 > β-terpineol-ODR1 > citronellal-ODR1 > l-limonene-ODR1 > γ-terpinene-ODR1. Taken together, the cumulative in vitro and computational bioefficacy analysis related to the chemoprofiles of EOs provides useful leads on harnessing the potential of EOs as bionematicides. The insight on biochemical ligand-target protein interactions described in the present work will be helpful in logical selection of biomolecules and essential oils for development of practically viable bionematicidal products.